A feasibility study of usability and UX evaluation technologies in multi-touch context: A quantitative and qualitative analysis - Filho, Guilherme; Guerino, Guilherme; Valentim, Natasha (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2023)
The use of multi-touch systems has been increasing in the last few years. These systems also need to pass through an evaluation to check their quality level. For this, usability and User Experience (UX) are two important aspects. Seeking to find out which technologies are being used for this purpose, we performed a Systematic Mapping Study (SMS). We discover that no technologies are being used to evaluate usability and UX on multi-touch interfaces that consider the specificities of this context, such as lack of touch precision and mechanical feedback. We proposed the User Experience and usability Multi-touch Evaluation Questionnaire (UXUMEQ) to fill this gap. This technology was evaluated through a feasibility study performed with 47 participants. Efficiency and effectiveness were compared to a combination of the System usability Scale (SUS) and Intuitive Questionnaire (INTUI). According to quantitative results, UXUMEQ presented a statistically significant difference over SUS+INTUI in terms of efficiency, while in effectiveness the comparison remained similar. In other words, UXUMEQ allows the users to find more problems, though it cannot be said that it saves time in this search compared to SUS+INTUI. UXUMEQ was considered easy to use, proposal-fulfilling, and highly assertive by the study participants. The qualitative data was analyzed and generated in a new version of UXUMEQ.